Gli infortuni sul lavoro in Brasile. Studio nello Stato di San Paolo del Brasile, regione di Botucatu, utilizzando il metodo dell'albero delle cause - Binder, Maria Cecília Pereira [UNESP]; Almeida, Ildeberto Muniz de [UNESP] (My University, 1999)
This paper discusses, within the prevaling Brazilian situation, the possibility of applying 'Causal Tree' (CT) method in investigating occupational accidents by safety personnel in the public health services and workers' unions. The method was developed during the seventies in France, for use by plant safety personnel. The authors used this method in Botucatu, State of Sao Paulo, Brazil, in order to investigate 40 serious occupational accidents that occurred in industrial plants during the second half of 1993, that had been registered by Social Security. In these cases, the predominance of situations in which the lack of safety measures were identified by inspection indicates that in most instances, the use of CT is unnecessary. However, the authors discuss its use by safety personnel from the public health services and workers' unions to investigate certain accidents to contribute to the knowledge base and help overcome the cultural based guilt which, in Brazil, has turned the victim into the person responsible for the accident.
Occupational accidents in Brazil. A study of applying the causal tree method in Botucatu, State of Sao Paulo
Keywords: Accident analysis; Causal tree method; Brazil; Clinical article; France; Human; Industrial worker; Methodology; Occupational accident; Occupational safety; Public health service; Social security; Trade union; Accidents, Occupational; Adult; Decision Trees; Humans; Incidence; Male; Systems Theory; Urban Population